Isolated left-sided partial anomalous pulmonary venous connection in a child - İsmihan Selen Onan; Onur Sen; Selman Gokalp; Burak Onan (KARE Publishing, 2017)
Isolated left-sided partial anomalous pulmonary venous connection with intact interatrial septum is a rare diagnosis in childhood. In these cases, a vertical vein drains the left upper pulmonary lobe into the brachiocephalic vein and finally to the right atrium. Surgical treatment is performed to prevent right ventricular failure and pulmonary artery disease in advanced age. In this report, the rare entity of isolated left-sided anomalous pulmonary venous connection in a 14-year-old girl and successful minimally invasive surgery without cardiopulmonary bypass are described.